A catalogue of teleosauroids (Crocodylomorpha: Thalattosuchia) from the Toarcian and Bajocian (Jurassic) of southern Luxembourg. (21st October 2019) - Johnson, Michela M.; Young, Mark T.; Brusatte, Stephen L.; Thuy, Ben; Weis, Robert
Abstract: Teleosauroids were a clade of semi-marine crocodylomorphs that attained near-global distribution during the Jurassic Period. They were particularly common during the Toarcian (Early Jurassic) and are well documented throughout the UK and Germany. However, Toarcian teleosauroids discovered in Luxembourg have been little studied and rarely discussed in the scientific literature. Here we present a comprehensive catalogue of Luxembourg thalattosuchian specimens, including nine teleosauroids (all from the Toarcian) and five Thalattosuchia indeterminate (four from the Toarcian and one from the Bajocian), many of which are noted in the literature for the first time. We describe these specimens and identify two distinct genera ( Steneosaurus and Platysuchus ) as present in the sample as well as three, or possibly four, distinct species. This represents a high diversity of teleosauroid taxa (both common and rare forms) from the Toarcian rarely seen elsewhere in the world.